Mechanical Properties and Microstructure Evolution of Cemented Tailings Backfill Under Seepage Pressure - Ke, Yuxian; Shen, Yang; Qing, Chen; Hu, Kaijian; Wang, Shi; Chen, Qiusong; Guan, Huadong (Frontiers in Materials, 2022)
Cemented tailings backfill (CTB) in underground mine inevitably experiences seepage field, which complicates its mechanical behavior. In this study, the mechanical properties and microstructure characteristics of CTB under different seepage water pressures (SWP) were investigated. The results show that, with the increase of SWP, the mechanical properties of CTB decrease but the decreasing trend reduces gradually. Higher SWP leads the microstructure of CTB looser and more porous, and the largest proportion of pores initiated and propagated by SWP are micropores, which means the damage in CTB under seepage is mostly caused by micropores. Besides, the mechanical properties of CTB under seepage decrease exponentially with the increase of porosity and present linearly inverse proportional relation to the pore area fractal dimension. Results above indicate that SWP has a significant deterioration effect on the mechanical properties and microstructure of CTB. The research could extend the knowledge of mechanical properties and microstructure characteristics of CTB under seepage, and provide a theoretical reference for mechanical indexes determination and stability analysis of CTB in water-rich underground mines.